2019
DOI: 10.1098/rsos.182192
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected spatial population ecology of a widespread terrestrial salamander near its southern range edge

Abstract: Under the current amphibian biodiversity crisis, common species provide an opportunity to measure population dynamics across a wide range of environmental conditions while examining the processes that determine abundance and structure geographical ranges. Studying species at their range limits also provides a window for understanding the dynamics expected in future environments under increasing climate change and human modification. We quantified patterns of seasonal activity, density and space use in the east… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 59 publications
0
15
2
Order By: Relevance
“…This species of terrestrial salamander is particularly widespread and can be found as far north as Quebec and as far south as North Carolina (Petranka, 1998). Southern populations of red‐backed salamanders exhibit seasonal periods of surface activity separated by a long period of surface inactivity during the summer months where individuals retreat to underground refugia to decrease risk of desiccation (Hernández‐Pacheco et al., 2019; Nagel, 1977). This salamander is a dispersal‐limited species with narrow space use of <5 m and mean maximum movement distance ranging from 0.7 to 1.9 m (Hernández‐Pacheco et al., 2019; Muñoz et al., 2016; Sutherland et al., 2016).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This species of terrestrial salamander is particularly widespread and can be found as far north as Quebec and as far south as North Carolina (Petranka, 1998). Southern populations of red‐backed salamanders exhibit seasonal periods of surface activity separated by a long period of surface inactivity during the summer months where individuals retreat to underground refugia to decrease risk of desiccation (Hernández‐Pacheco et al., 2019; Nagel, 1977). This salamander is a dispersal‐limited species with narrow space use of <5 m and mean maximum movement distance ranging from 0.7 to 1.9 m (Hernández‐Pacheco et al., 2019; Muñoz et al., 2016; Sutherland et al., 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Each array consisted of 50 pine cover boards (30.5 × 30.5 × 2.1 cm) spaced 1 m apart in a rectangular grid (Sutherland et al., 2016). Each cover board served as an “open trap” that was surveyed on multiple capture occasions in two field seasons defined by availability for capture on the surface (season 1: autumn 2016–spring 2017; season 2: autumn 2017–spring 2018; Hernández‐Pacheco et al., 2019). During field season 1, we surveyed Sites 1, 2, and 3 on 6 capture occasions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, clades of Plethodon typically include species that are very widespread and abundant, but also range‐restricted endemics with among the smallest ranges of any vertebrates in mainland North America (Highton, 1995). Plethodon cinereus , the Eastern Red‐backed Salamander, can reach densities of 2–3 individuals per m 2 across large areas of Eastern North America from North Carolina to central Quebec (Hernández‐Pacheco, Sutherland, Thompson, & Grayson, 2019; Mathis, 1991; Figure 1a). In contrast, narrowly distributed endemics within this group are often species of conservation concern.…”
Section: Introductionmentioning
confidence: 99%